Bimbingan Kelompok Pada Pengurus Organisasi Siswa - Beti Malia Rahma Hidayati (Universitas Islam Tribakti Lirboyo Kediri, 2017)
Guidance and counseling services is an integral part (integral) of the entire educational program to find personal, recognize the environment, group work, and future planning. IPNU-IPPNU student organization at MTs Sunan Ampel Pare he newly formed still focus arrange administration and a work program that is still very simple. Stewardship is still not effective, still waiting for orders from teachers and not yet independent, madrasah has given place, and ready to provide funds, but students can not use it. As an educational psychologist, researchers do deepening of group cases in the madrasah through a psychological assessment process. To follow up on these issues, created the design of interventions in the form of group counseling activities with the theme capacity building